2022
DOI: 10.1002/jrs.6357
|View full text |Cite
|
Sign up to set email alerts
|

Identification of illicit street drugs with swept‐source Raman spectroscopy

Abstract: The identification of the illicit substances in low‐purity seized drugs with Raman spectroscopy is an outstanding problem. The low concentration of the target molecule demands high sensitivity and the presence of impurities produces a strong fluorescence background that makes identification challenging. Although Raman analyzers with 785 and 830 nm excitation wavelengths provide high sensitivity, the longer 1064 nm wavelength produces lower fluorescence. In this work, we demonstrate a Raman spectrometer that si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…7,9 The presence of fluorescent dye or unknown excipients even at trace levels in ecstasy tablets, can cause fluorescence that then mask the Raman signals. 9,29 Specific dyes such as black and yellow dyes in ecstasy tablets gave absorbance signals in the 1300-2600 nm NIR range and partly obscure the spectral signal from MDMA. 30 Previous studies have reported that samples with black or dark colours caused difficulty for positive detection in Raman spectroscopy.…”
Section: Number Of Samplementioning
confidence: 99%
“…7,9 The presence of fluorescent dye or unknown excipients even at trace levels in ecstasy tablets, can cause fluorescence that then mask the Raman signals. 9,29 Specific dyes such as black and yellow dyes in ecstasy tablets gave absorbance signals in the 1300-2600 nm NIR range and partly obscure the spectral signal from MDMA. 30 Previous studies have reported that samples with black or dark colours caused difficulty for positive detection in Raman spectroscopy.…”
Section: Number Of Samplementioning
confidence: 99%
“…Kay et al addressed the same issue with a new technique known as Swept Source Raman Spectroscopy (SSRS). 242 In this approach, there is a single collection channel while the excitation laser is tunable.…”
Section: ■ Chemistry: Seized Drugs and Toxicologymentioning
confidence: 99%
“…When compared to the 785 nm laser, positive identification increased almost 5-fold for both the 1064 nm laser and SSE. Kay et al addressed the same issue with a new technique known as Swept Source Raman Spectroscopy (SSRS) . In this approach, there is a single collection channel while the excitation laser is tunable.…”
Section: Chemistry: Seized Drugs and Toxicologymentioning
confidence: 99%
“…CARS can also be done with a wavelength-swept source to improve the acquisition speed, spectral resolution, and collection efficiency, as we demonstrated in a prior work 17 . More recently, spontaneous Raman spectroscopy has been performed using a low power wavelength-swept source to increase the photon collection and reduce the noise around 2× 18 , 19 . Replacing the fixed laser in Raman spectroscopy with a swept-source can be advantageous, 20 and using a wide-area detector enables enhanced signal collection, supporting remote spectrum acquisition for various applications, such as water quality monitoring and indoor farm plant growth tracking 21 .…”
Section: Introductionmentioning
confidence: 99%
“… 17 More recently, spontaneous Raman spectroscopy has been performed using a low power wavelength-swept source to increase the photon collection and reduce the noise around 2×. 18 , 19 Replacing the fixed laser in Raman spectroscopy with a swept-source can be advantageous, 20 and using a wide-area detector enables enhanced signal collection, supporting remote spectrum acquisition for various applications, such as water quality monitoring and indoor farm plant growth tracking. 21 In addition, replacing the spectrometers with a detector facilitates the development of handheld and miniaturized Raman spectroscopy setups, and it yields the same spectrum as using a conventional Raman spectrometer.…”
Section: Introductionmentioning
confidence: 99%